Biodegradation of atrazine, glyphosate and pendimetaline employing fungal consortia (Research, Society and Development, 2020)
The objective of the present study was to evaluate the bioremediation of soils artificially contaminated with atrazine, glyphosate and pendimethalin by fungal consortia in biodegradation processes in microcosms. Biodegradation was evaluated from microbial respiration over a period of 15 days and genotoxicity analysis in Allium cepa roots exposed to elutriate samples at zero and 50 μg mL-1 concentrations of the herbicides after the biodegradation process. The results were submitted to analysis of variance, the Tukey test and the Fischer test (p